Trophoblast 'pseudo-tumorigenesis': Significance and contributory factors - Rao A Jagannadha; Soundararajan Rama (BMC, 2004)
Abstract Trophoblast cells of the human placenta proliferate, migrate, and invade the pregnant uterus and its vasculature in order to nourish the developing fetus, in a way that is imitated by malignant tumors. Many similarities exist between embryo implantation and the growth of cancer cells. We begin this article by reviewing decades of studies that have helped unearth the mechanisms that contribute to the tumor-like phenotype of human trophoblast cells. Interestingly, these attributes are only transient in nature, with stringent spatial and temporal confines. The importance of intrinsic molecular controls that effectively circumscribe the extent and duration of trophoblast incursion, becomes increasingly evident in abnormal pregnancies that are characterized by aberrant trophoblast proliferation/invasion. We summarize and discuss the significance of abnormalities in these regulatory mechanisms, and finally, speculate about the use of human trophoblastic cells as model systems for the study of a variety of cellular processes. While on one hand, human placental cells are bestowed with a capacity to proliferate indefinitely and invade extensively, on the other, these cells are also replete with mechanisms to regulate these tumor-like attributes and eventually progress to a senescent apoptotic state. This is therefore, a 'well-behaved' tumor. The comparison in the present review is between the invasive cytotrophoblastic cell type and the tumor cell type.